Meningkatkan Hasil Belajar Siswa melalui Penerapan Model Kooperatif Tipe STAD dalam Pembelajaran Seni Tari pada Kelas X E2 di SMA Pembangunan Laboratorium UNP - Putri, Anglya; Astuti, Fuji (Lembaga Yasin AlSys, 2025)
This study was motivated by the low learning outcomes of students in Dance Art subject in class X E2 at SMA Pembangunan Laboratorium UNP. One contributing factor is the lack of active student participation during the learning process. The objective of this study is to improve student learning outcomes through the implementation of the cooperative learning model Student Teams Achievement Divisions (STAD). The study employed Classroom Action Research (CAR) conducted in two cycles, involving 33 students. Data collection techniques included written tests, performance tests, observation, and documentation. Results from Cycle I indicated low student engagement, with only 42% paying attention and 31% actively responding to questions. However, Cycle II showed a significant improvement, with all students (100%) attentive during lessons and 85% actively participating. Learning outcomes also increased from 18% in Cycle I to 87% in Cycle II, categorized as very good. These findings indicate that the STAD model is effective in enhancing both student learning outcomes and engagement in Dance Art instruction. The implication is that the STAD cooperative approach is a viable strategy for promoting active learning in the arts.